Review of Islamic Law on the Advancement of IVF Reproductive Technology in a Positive Legal Perspective - Faridz Anwar, Ahmad Faridz Anwar1 (Jurnal Legisci, 2023)
Every couple who has just married will feel incomplete if their marriage is not blessed or does not have children as proof of the love of the couple. This study aims to find out the review of Islamic law on IVF reproductive technology and positive legal perspectives in regulating IVF reproductive technology. The research method that is considered suitable for this writing is descriptive qualitative method. In this study there are two conclusions. First, in the perspective of Islamic law there are categories of fiqh that allow and there are also those that prohibit IVF. Whereas in Islamic law the Maqasyid AsSyari'ah category, IVF is permissible, because for the sake of benefit, the category protects offspring. Second, legally, the implementation of artificial insemination in Indonesia must always refer to Law no. 36 of 2009 concerning Health. This law stipulates that the implementation of an artificial insemination program must be carried out in accordance with the norms of law, religion, decency and decency. This law regulates that in the implementation of the artificial insemination program in Indonesia, it is not permitted to use the uterus belonging to a woman who is not his wife.